Vulnerability to extreme heat by socio-demographic characteristics and area green space among the elderly in Michigan, 1990-2007 - Gronlund, Carina J. (Environ Res, 2014)
OBJECTIVES: We examined how individual and area socio-demographic characteristics independently modified the extreme heat (EH)-mortality association among elderly residents of 8 Michigan cities, May-September, 1990-2007. METHODS: In a time-stratified case-crossover design, we regressed cause-specific mortality against EH (indicator for 4-day mean, minimum, maximum or apparent temperature above 97th or 99th percentiles). We examined effect modification with interactions between EH and personal marital status, age, race, sex and education and ZIP-code percent “non-green space” (National Land Cover Dataset), age, race, income, education, living alone, and housing age (U.S. Census). RESULTS: In models including multiple effect modifiers, the odds of cardiovascular mortality during EH (99(th) percentile threshold) vs. non-EH were higher among non-married individuals (1.21, 95% CI = 1.14-1.28 vs. 0.98, 95% CI = 0.90-1.07 among married individuals) and individuals in ZIP codes with high (91%) non-green space (1.17, 95% CI = 1.06-1.29 vs. 0.98, 95% CI = 0.89-1.07 among individuals in ZIP codes with low (39%) non-green space). Results suggested that housing age may also be an effect modifier. For the EH-respiratory mortality association, the results were inconsistent between temperature metrics and percentile thresholds of EH but largely insignificant. CONCLUSIONS: Green space, housing and social isolation may independently enhance elderly peoples’ heat-related cardiovascular mortality vulnerability. Local adaptation efforts should target areas and populations at greater risk.